Abdominal angiostrongyliasis: report of two cases with different clinical presentations - Rodriguez, Rubens; Dequi, Roberta Martins; Peruzzo, Lucas; Mesquita, Paulo Moacir; Garcia, Errol; Fornari, Fernando (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
Abdominal angiostrongyliasis is a sporadic infectious disease caused by the nematode Angiostrongylus costaricensis. It usually presents as acute abdomen, secondary to mesenteric ischemia, and pronounced eosinophilia. In some cases its course is insidious and transient, and the diagnosis is suspicious. The disease is confirmed by the detection of A. costaricensis elements in surgical specimen. The treatment is supportive, with avoidance of antihelminthic administration due to a possible erratic migration followed by worsening of the disease. We report two cases, both with intense eosinophilia and serum IgG-ELISA positive to A. costaricensis. The first case presented ileal perforation and was surgically treated. The second one showed hepatic nodules at ultrasound and was only symptomatically treated, evolving to an apparent protracted resolution. These two cases exemplify different clinical forms of the disease, one of them with liver involvement.